Infection and apparent invasion of vero cells by paracoccidioides brasiliensis - Mendes-Giannini, M. J.S. [UNESP] (1994)
Paracoccidioides brasiliensis probably uses many different mechanisms to establish itself in the host and cause disease. In this work, we assess an in vitro model system which uses cultured mammalian cells to investigate the virulence factors of P. brasiliensis. We were able to demonstrate an invasion process of the yeast form of this fungus in Vero cell cultures. We deduced that the overall invasive process involved three steps: adhesion, followed by invasion of individual epithelial cells and spread to adjacent cells. © 1994 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.